Impact of Circuit Training Variations on Muscle Endurance, Cardiovascular Endurance, and Decreased Body Fat - Anandiaz Iman Santoso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the modern era like today, the tight schedule of matches makes physical trainers have to mix programs in such a way as to prepare their athletes for maximum performance, often not enough time is available to develop each of these elements optimally. The purpose of this study was to determine whether there was a significant difference between SR-Circuit Training and SO-Circuit Training on muscle endurance, cardiovascular endurance, and decreased body fat. The research method used in this research is the experimental method. This method is used on the basis of the consideration that the nature of experimental research is to try something to determine the effect of a treatment or treatment. The results showed that there was a significant difference between SR-Circuit Training and SO-Circuit Training on muscle endurance, cardiovascular endurance, and decreased body fat.